The Work Productivity Analysis in Employees of the Semarang Regency Tourism Office - parjani, fira putri anjani; Efriyani Sumastuti,; Heri Prabowo, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Research conducted at the Semarang Regency Tourism Office, there are still several employees who experience locus of control caused by human relations, leadership style, work environment, and even the workload borne by employees every day can have an impact on work standards in the agency. Therefore, to create good work productivity, the approach used is a quantitative approach. The independent variables in this study are locus of control, human relations, leadership style, work environment, workload and the bound variable is work productivity. The results showed that locus of control had a positive and significant influence on work productivity, human relations had a positive but not significant influence on work productivity, leadership style had a positive and significant influence on work productivity, work environment had a positive but not significant influence on work productivity, and workload had a positive but insignificant influence on work productivity.